Butterfly diversity in the three selected areas in Dhaka city, Bangladesh (Bangladesh Journal of Zoology, 2021)
The diversity of butterfly species was studied from January to June 2015 in the three selected areas, viz. Ramna Park, Jagannath University Campus, and Baldha Garden in Dhaka city, Bangladesh. A total 75 species of butterfly belonging to 42 genera under 8 families were recorded from the study areas during the study period. Of them, 52 species (6253 individuals) of 8 families were found in the Ramna Park, 37 species (1430 individuals) of 7 families in the Jagannath University Campus and 20 species (320 individuals) of 6 families in the Boldha Garden. In these three study areas, 17 species, 14 genera and 6 families were in common. At the Ramna Park, the highest species richness included the family Lycaenidae (21.15%, 11 spp.) followed by Papilionidae (17.31%, 9 spp.), Pieridae (17.31%, 9 spp.), Nymphalidae (17.31%, 9 spp.), Hesperiidae (13.46%, 7 spp.), Danaidae (7.69%, 4 spp.), Satyridae (3.85%, 2 spp.), and the lowest was in the family Acriidae (1.92%, 1 spp.). At the Jagannath University Campus the highest number of species were recorded in the family Lycaenidae (21.62%, 8 spp.) and Hesperiidae (21.62%, 8 spp.) followed by Pieridae (18.92%, 7 spp.), Papilionidae (13.51%, 5 spp.), Nymphalidae (10.81%, 4 spp.), Danaidae (10.81%, 4 spp.), and the lowest was in Satyridae (2.70%, 1 spp.). The topmost butterfly species were recorded in the family Pieridae (25%, 5 spp.) followed by Lycaenidae (20%, 4 spp.), Nymphalidae (20%, 4 spp.), Papilionidae (15%, 3 spp.), and the lowest from the family Hesperiidae (10%, 2 spp.) and Danaidae (10%, 2 spp.) at the Baldha Garden. The maximum butterfly species were found in February to June (51 spp.), February (34 spp.), and April (16 spp.), and the lowest were in January (46 spp.), June (21 spp.) and January (8 spp.), respectively for the Ramna Park, Jagannath University Campus and the Baldha Garden. The peak of the population observed in May (n =1285), March (n = 325), and May (n = 71), and the lowest was in January (n = 662), June (n = 145) and January (n = 21), respectively for the Ramna Park, Jagannath University Campus, and Baldha Garden. The Shanon’s Diversity Index (H) and Simpson’s Index (λ) indicated high butterfly diversity at the Ramna Park (H = 3.68, λ = 0.03), Jagannath University Campus (H = 3.20, λ = 0.06) and Baldha Garden (H = 2.50, λ = 0.13), respectively. The high Species Evenness in the Ramna Park (E = 0.93), Jaganath University Campus (E = 0.89) and the Baldha Garden (E = 0.84) indicated that the species were evenly distributed. The calculated Sorenson’s Coefficient (CC) was 0.47, which indicates that these three communities have quite a bit of overlap or similarity.Bangladesh J. Zool. 48(2): 413-428, 2020